Effects of the COVID-19 pandemic on senior dental students in Korea: Examining stress, burnout, and depression - Gloria Hyunjung Kwak; Seung-Ho Baek; Eun-Jung Kwak (Elsevier, 2024)
Background/purpose: The COVID-19 pandemic has had a profound and enduring impact on various aspects of society, including medical education and the training of dental students. The field of dentistry, given its nature, is particularly susceptible to the challenges posed by a pandemic. Prolonged exposure to the pandemic is believed to have increased stress and burnout among medical and dental students. This study aimed to investigate and analyze the relationship between COVID-19 and stress, burnout, and depression in Korean dental students. Materials and methods: A cross-sectional survey was conducted among 162 third and fourth-grade students from the School of Dentistry at Seoul National University. The survey comprised four main sections: general information, the Maslach Burnout Inventory (MBI), the Patient Health Questionnaire-9 (PHQ-9), and the Impact of Event Scale-Revised (IES-R). Results: The results indicated significant differences in age, study time, career satisfaction, and counseling needs between third and fourth-grade students. The fourth-grade students exhibited higher scores in the IES-R survey, PHQ-9 total score, emotional exhaustion, and depersonalization subscale items of the MBI. Furthermore, the group with abnormal responses to COVID-19 demonstrated lower levels of career satisfaction. Conclusion: Fourth-grade dental students experienced higher levels of depression, vulnerability to the effects of COVID-19, and burnout. These findings highlight the need for addressing the mental health challenges faced by dental students during the COVID-19 pandemic.